Enhancing EFL Learners’ Vocabulary Through Incidental Acquisition via Reading: A Study in Saudi Arabia (المجلة الدولية للعلوم التربوية والآداب, 2026)
This study investigates the effectiveness of reading to enhance learner vocabulary size in a second language. The study took place in Al-Khafji College, Saudi Arabia, with 36 female student participants. Participants were pretested on the vocabulary displayed in the texts, and then exposed to three different reading passages before sitting the same test again at a later time. The results show significant vocabulary size improvement despite the brevity of the reading passages given and the short amount of time that had elapsed. Also, there is a relationship was found between the students’ vocabulary acquisition and the frequency of each word’s appearance in the texts.